Peran Disregulasi Imunitas dalam Terapi Kusta pada Area Endemis: Artikel Review: The Role of Immune Dysregulation in Leprosy Treatment in Endemic Areas: Review Article - Flora Ramona Sigit Prakoeswa; Faradiba Maharani (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2022)
Leprosy, a chronic infectious disease caused by Mycobacterium leprae, causes health problems and endemic in several countries. The number of new cases of leprosy is constantly reported in endemic countries. Therapeutic efforts in leprosy patients are carried out with the aim of reducing the level of transmission and disability of leprosy patients. Leprosy therapy with the use of a multidrug regimen (MDT) has been shown to be able to reduce the number of leprosy cases but has not been able to suppress the rate of growth of new leprosy cases. The constant number of new cases of leprosy in endemic areas indicates community infection and the inability of MDT as a single strategy to complete treatment and stop the transmission of leprosy. The transmission of leprosy is known to be multifactorial involving: microbial factors, host factors, and environmental factors. These factors are thought to cause immune dysregulation and increase the risk of leprosy infection in people living in endemic areas. An understanding of immune dysregulation is needed to achieve succesful treatment and the eradication of leprosy.